Gambling in the garden: Pesticide use and risk exposure in Ugandan smallholder farming. (February 2021) - Andersson, Elina; Isgren, Ellinor
Abstract: The use and promotion of pesticides is on the increase in many sub-Saharan African countries, including in the smallholder sector. This paper stems from placed-based research in Uganda and aims at advancing current knowledge on smallholder farmers' motivations for pesticide use, the extent and character of such use, as well as on lived experiences regarding the impacts of pesticides. Data was generated through a household survey, in-depth interviews and focus group discussions with farmers, complemented by field observations and interviews with local agricultural actors. Conceptually, we draw on political ecology to link local practice to broader conditions and processes and their social-environmental outcomes. Our findings demonstrate that a large majority of farmers have resorted to pesticides as their primary strategy for pest control. Current practices entail substantial human health and environmental risks which tend to be socially differentiated, including along gender lines. Many farmers are concerned about the impacts and uncertainties surrounding pesticides, but face numerous barriers to behavioral change. While intensifying pest pressure is one such immediate barrier, our findings also suggest that deep structural forces shape farmers' adoption of pesticides and prevent adequate protective measures. Rapid market liberalization combined with poor regulation enforcement have resulted in widespread promotion of agro-chemicals and a large informal market for cheap, poor-quality products, including counterfeits. Low public spending on the agricultural sector, a malfunctioning extension system and systematic lack of development and promotion of strategies not centered on synthetic pesticides furthermore severely constrain farmers' access to support on, and indeed options for, pest control. This lacking capacity and effort to adequately protect smallholders from pesticide exposure and ensure their ability to make informed decisions on pest management clearly places the burden of risk disproportionately on an already vulnerable group. Highlights: Pesticide use among smallholders is far more widespread than commonly assumed. Farmers' pesticide practices entail substantial risk to human and environmental health. Smallholders largely rely on unauthorized supply channels to access pesticides. Their access to technical support and protective measures is largely inadequate. Farmers are well-aware of pesticide risks but typically lack options for pest control.